Threshold-Based Allocation Policies for Inventory Management of Red Blood Cells - Sarhangian, Vahid; Abouee-Mehrizi, Hossein; Baron, Opher; Berman, Oded (Manufacturing and Service Operations Management, 2018)
Under current regulations, red blood cell (RBC) units can be transfused to patients up to 42 days after donation. However, recent studies suggest an association between the age of transfused RBCs and adverse clinical outcomes for their recipients. Therefore, there is an interest in inventory management policies that could reduce the age of transfused RBCs without compromising their availability. In this work, we study the performance of a practical family of threshold-based allocation policies, designed to trade off the age of RBC transfusions with their availability at hospitals. To this end, we consider a stylized model of a hospital blood bank that procures its required blood from local donations. For this model, we develop a new method to exactly evaluate the performance of the threshold policy in terms of the distribution of the age of allocated units and the proportion of outdates and lost demand. Through numerical and structural results, we obtain new insights on the performance of the threshold policy and in particular on how it compares with shortening the shelf life of RBCs (e.g., from 42 to 28 days). We verify and discuss the robustness of these results to the model assumptions in a simulation study calibrated using data from a Canadian hospital blood bank. The online appendix is available at https://doi.org/10.1287/msom.2017.0650 .